A review of the gobiid fish genus Aulopareia (Gobiidae: Gobiinae) with description of a new species from Kuwait and discussion of the status of Gobius cyanomos Bleeker - Larson, Helen K.; Jaafar, Zeehan (Zootaxa, 2022)
The tropical Indo-west Pacific gobiid fish genus Aulopareia Bleeker is reviewed, with all recognised species redescribed herein, apart from one uncertain species. Additionally, a new species from Kuwait is described (A. vadosa n. sp.). Of the 10 nominal species names usually assigned to this genus, only three appear to be valid Aulopareia (A. koumansi, A. ocellata and A. unicolor). From descriptions and illustrations, Acentrogobius microps Chu and Wu appears to be an Aulopareia but no material was available for study. The species that has been variously named as Acentrogobius cyanomos, Aulopareia cyanomos or Aulopareia spilopterus is redescribed. The status of two other species that may be related is also discussed: Gobius cyanoclavis Cantor and Gobius phaiomelas Bleeker. Aulopareia has been noted as being related to Parachaeturichthys.